2018
DOI: 10.1021/acsenergylett.8b01466
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Vertical Growth of Fe–Ni Layered Double-Hydroxide Arrays on Fe–Ni Alloy Foil: Interfacial Layer Enhanced Electrocatalyst with Small Overpotential for Oxygen Evolution Reaction

Abstract: Layer double hydroxide (LDH) has been widely applied to electrocatalysis, especially toward the oxygen evolution reaction (OER), owing to its flexible layered structure and multifunctionality. Herein, FeNi LDH nanosheet arrays are directly synthesized on various metal foils by a facile hydrothermal method. Compared with single Fe or Ni substrates, the obtained FeNi LDH/ FeNi foil exhibited an ultrasmall onset overpotential of ∼90 mV, high catalytic activity (overpotential of 130 mV @ 10 mA/cm 2 ), and durable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
75
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(78 citation statements)
references
References 65 publications
3
75
0
Order By: Relevance
“…The composition of the LDH catalysts was further verified by X‐ray photoelectron spectroscopy (XPS), as shown in Figure S5 in the Supporting Information. In the high‐resolution Ni 2p spectra (Figure S6 in the Supporting Information), Ni 2p 3/2 and 2p 1/2 peaks were centered at binding energies of 856.8 and 874.6 eV, respectively, indicating the existence of Ni 2+ . The binding energy peaks of Fe 2p 3/2 and 2p 1/2 were located at 709.8 and 712.2 eV, respectively (Figure S7 in the Supporting Information), demonstrating the presence of Fe 3+ .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The composition of the LDH catalysts was further verified by X‐ray photoelectron spectroscopy (XPS), as shown in Figure S5 in the Supporting Information. In the high‐resolution Ni 2p spectra (Figure S6 in the Supporting Information), Ni 2p 3/2 and 2p 1/2 peaks were centered at binding energies of 856.8 and 874.6 eV, respectively, indicating the existence of Ni 2+ . The binding energy peaks of Fe 2p 3/2 and 2p 1/2 were located at 709.8 and 712.2 eV, respectively (Figure S7 in the Supporting Information), demonstrating the presence of Fe 3+ .…”
Section: Resultsmentioning
confidence: 99%
“…In the high‐resolution Ni 2p spectra (Figure S6 in the Supporting Information), Ni 2p 3/2 and 2p 1/2 peaks were centered at binding energies of 856.8 and 874.6 eV, respectively, indicating the existence of Ni 2+ . The binding energy peaks of Fe 2p 3/2 and 2p 1/2 were located at 709.8 and 712.2 eV, respectively (Figure S7 in the Supporting Information), demonstrating the presence of Fe 3+ . The XPS results were in accordance with the XRD observations, further confirming the formation of NiFe LDH.…”
Section: Resultsmentioning
confidence: 99%
“…As can be seen in Table 1, several substrates, such as nickel foam, [9,15] gold, [14a] and glassy carbon, [16] electrodes, have been used for deposition of Ni 1-x Fe x OOH. Recently, Xiang et al [17] reported the use of FeÀ Ni alloy foil as a substrate to grow vertically aligned NiÀ Fe (oxy)hydroxide, which allows a facile access to the catalytic sites and a favourable adsorption of OH intermediate during OER. However, these electrodes lack transferability to "real world"/industrial applications.…”
Section: Introductionmentioning
confidence: 99%
“…Those iron‐substrate‐derived LDHs showed remarkable electrocatalytic stability for more than 6 000 hours (>8 months) at a large current density of 1 000 mA cm −2 owing to strongly coupled interface between LDH and substrate, and the ultrasmall crystalline domains within nanosheets. Up to now, a variety of LDHs have been successfully constructed on various substrates such as FeNi‐LDH/FeNi foil, NiFe‐LDH/graphene foil, NiAl‐LDH/carbon nanotube paper, CoAl‐LDH/reduced graphene oxide, ZnCr‐LDH/fluorine‐doped tin oxide (FTO), CoFe‐LDH/Cu mesh, and those synthesized pristine LDH‐INEs have brought about widespread attention in energy storage and conversion fields.…”
Section: Ldh‐inesmentioning
confidence: 99%